Exploring how novel reading enhances youth literacy, deepens insight, and fosters creative thinking - I Made Sumartana; I Putu Yoga Laksana; Adisti Primi Wulan; Zulfiqar Ali; Bareq Raad Raheem; Sidratul Muntaha Uzma; Muhammad Mustafa; Siti Mariam (PT. MAWAMEDIA JAYAMUSTA BUANASIHA, 2026)
Reading has various benefits in everyday life, especially for teenagers. This study aims to explore the impact of reading novels on adolescents' literacy, creativity, critical thinking and mental health. Through the analysis of data obtained from 12 respondents aged 19-20 years old, results show that 100% of respondents agreed that reading novels can improve their literacy and creativity. The knowledge gained from reading helps teens develop creative thinking and critical thinking skills. The survey results also indicated that 100% of respondents found reading novels helpful in coping with emotions and stress, with genres as diverse as romance, fiction, history and politics. In addition, this study confirms the importance of emotional intelligence in helping adolescents recognize and manage their feelings. This finding is in line with previous research showing that reading interest is positively related to critical thinking and critical reading skills. Overall, the results of this study suggest that reading novels not only improves cognitive skills but also provides significant emotional support for adolescents in facing the challenges of daily life.